Students’ Electronic Worksheets Based on Local Wisdom Assisted with Liveworksheets for Hybrid Learning - Syar, Nur Inayah; Sulistyowati, Sulistyowati; Supriatin, Atin; Maghfirotuna'imah, Mirda; Ningsih, Indri Widia; Fachrizal, Fachrizal (Universitas Pendidikan Indonesia, 2023)
The purpose of this study was to develop electronic Students Worksheets (LKPD) based on local wisdom assisted by Liveworksheets in the thematic learning of class V Madrasah Ibtidaiyah for Hybrid Learning. This research was an RD research with the development of a Worksheet using a 4D model. The instrument used was a list of interview questions and questionnaires. The number of students used for the product trial was 58 students from four Islamic Madrasahs in Palangka Raya City. The results showed that the electronic Students Worksheets was developed using a number of stages. The first stage is the definition namely needs analysis and curriculum analysis. The second stage is designing the contents of the electronic Students Worksheets and making a feasibility test instrument. The third stage is development which consists of feasibility test and revision. The fourth stage is dissemination which consists of product testing, packaging and distribution to schools. Based on the results of the feasibility test, the electronic Students Worksheets was in the